RELATIONS OF COGNITIVE SKILLS AND COORDINATION IN RHYTHM - Dušanka Tumin; Dejan Madić; Boris Popović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
According to many authors who have studied the relations of cognitive and motor skills (Ismail, Madić), there is a relationship between these two anthropological spaces. Motor skill is related with cognitive factor, especially in these tasks which have unusual rhythmic structure where speed and accuracy of performance is needed. As many test tasks for evaluation of coordination are designed in exactly the same manner, it may be assumed that there is a relation with cognitive skills of students performing these exercises. Relations between cognitive skills and coordination in rhythm are evaluated on the sample of 217 students of the Faculty of Sport and Physical Education in Novi Sad. For evaluation of cognitive skills, we have used the battery of tests KOG 3 (Wolf, Momirović & Džamonja, 1992). For coordination in rhythm, we have used the following tests: tapping on horizontal plates, tapping on plates in three plane surfaces, and tapping with hands and feet.(Metikoš et al., 1989).Using regression analysis, we have found the relationship between these two anthropological spaces.